BRCA2 Variants and cardiovascular disease in a multi-ethnic study - Zbuk Kevin; Xie Changchun; Young Robin; Heydarpour Mahyar; Pare Guillaume; Davis A; Miller Ruby; Lanktree Matthew B; Saleheen Danish; Danesh John; Yusuf Salim; Engert James C; et al. (BMC, 2012)
Abstract Background Germline mutations of BRCA1/2 are associated with hereditary breast and ovarian cancer. Recent data suggests excess mortality in mutation carriers beyond that conferred by neoplasia, and recent in vivo and in vitro studies suggest a modulatory role for BRCA proteins in endothelial and cardiomyocyte function. We therefore tested the association of BRCA2 variants with clinical cardiovascular disease (CVD). Methods Using data from 1,170 individuals included in two multi-ethnic population-based studies (SHARE and SHARE-AP), the association between BRCA2 variants and CVD was evaluated. 15 SNPs in BRCA2 with minor allele frequencies (MAF) > 0.01 had been previously genotyped using the cardiovascular gene-centric 50 k SNP array. 115 individuals (9.8%) reported a CVD event, defined as myocardial infarction (MI), angina, silent MI, stroke, and angioplasty or coronary artery bypass surgery. Analyses were adjusted for age and sex. The SNPs rs11571836 and rs1799943 were subsequently genotyped using the MassARRAY platform in 1,045 cases of incident MI and 1,135 controls from the South Asian subset of an international case-control study of acute MI (INTERHEART), and rs11571836 was imputed in 4,686 cases and 4500 controls from the Pakistan Risk of Myocardial Infarction Study (PROMIS). Results Two BRCA2 SNPs, rs11571836 and rs1799943, both located in untranslated regions, were associated with lower risk of CVD (OR 0.47 p = 0.01 and OR 0.56 p = 0.03 respectively) in the SHARE studies. Analysis by specific ethnicities demonstrated an association with CVD for both SNPs in Aboriginal People, and for rs11571836 only in South Asians. No association was observed in the European and Chinese subgroups. A non-significant trend towards an association between rs11571836 and lower risk of MI was observed in South Asians from INTERHEART [OR = 0.87 (95% CI: 0.75-1.01) p = 0.068], but was not evident in PROMIS [OR = 0.96 (95% CI: 0.90-1.03) p = 0.230]. Meta-analysis of both case-control studies resulted in a combined OR of 0.94 (95% CI: 0.89-1.004, p = 0.06). Conclusions Although there was an association between two SNPs in BRCA2 and CVD in a multi-ethnic population, these results were not replicated in two South Asian case-control studies of incident MI. Future studies exploring the association between BRCA variants and cardiovascular disorders are needed to clarify the role, if any, for BRCA variants in CVD pathogenesis.